Islamic Corporate Social Responsibility (ICSR): Integrating Islamic Values in CSR Beyond the Triple Bottom Line Perspective - Leniwati, Driana; Amelia, Shelvi Annisa; Affan, Muhammad Wildan (Indonesian Journal of Sustainability Accounting and Management, 2023)
The purpose of this research is to analyse corporate social responsibility based on Islamic business ethics. The method used is a case study with a qualitative descriptive approach. The informants in this study were the owners, employees, and customers of the restaurant. The result of the study is ICSR that corporate responsibility includes profit, people, and the planet based on the Islamic principles of shidiq, amanah, tabligh, and fatonah for justice (ad adl) and goodness (al ihsan). Accountability goes beyond the triple bottom line perspective because responsibility for profits, people, and the planet is not limited to obligations between humans and humans because of company policies, but corporate accountability as human obligations to God, including Islamic values as the spirit of ICSR which differentiates it from CSR in general. The main contribution of this research is to broaden the concept of CSR which sees accountability not only as profit, people, and the planet but beyond accountability to God because basically, humans are servants of God who must be responsible for all their actions and their lives only to God in accordance with Islamic values that taught by the Prophet.